Bere per dimenticare . Drink to Forget - Calabresi, Michele; Heeren, Patrick; Molino, C. (Morgana Production, 2006)
Verzio FF submission Hitler, Mussolini, Stalin and other dictators appear on the labels of wine bottles sold in Italy. “Drink to Forget" attempts to unravel the complex emotional, ethical and legal issues raised by the selling and buying of these images through interviews with various actors including the producers and buyers, legal experts, politicians, partisans and members of Italy's Jewish community.